Pendampingan Muslimah Berbasis Nilai Tarbiyah dan Ekologi Keluarga untuk Melawan Budaya Konsumtif dan Gaya Hidup Flex Culture di Kabupaten Bogor - Rahmawati Alwi; Marwani Syatar; Jamaludin Jamaludin (Jurnal Pendidikan Educandum, 2026)
The development of digital technology and access to e-commerce has strengthened the consumer culture and flex culture lifestyle among urban Muslim women in Cibinong and Ciawi Districts, Bogor Regency, which can be seen in the tendency to buy non-primary goods, go into debt to support their lifestyle, and show off luxury on social media. This condition weakens the internalization of tarbiyah values ​​and family ecology, and threatens the realization of a sakinah, mawaddah, warahmah family. This service aims to: (1) map the conditions of consumer culture and flex culture among Muslim women members of the taklim assembly, (2) formulate and implement mentoring strategies based on tarbiyah values ​​and family ecology, and (3) assess the impact on the resilience of Muslim women's families. The program uses a Participatory Action Research (PAR) approach with the main partners of the Ma'hadussholawah taklim assembly, Basama, and the Al-Qur'an Park Teachers Association (IGTA). The activity stages include problem mapping, module preparation, thematic training, mentoring sessions and family consumption management practices, monitoring through daily journals and checklists, as well as joint reflection and evaluation. Data was collected through participatory observation, interviews, questionnaires, Focus Group Discussions (FGD), and documentation, then analyzed qualitatively thematically and quantitatively descriptive to measure changes in knowledge, attitudes, and consumption practices.The results of the service show an increase in Muslim women's knowledge regarding the concept of tarbiyah, family ecology, and Islamic consumption ethics, accompanied by strengthening critical attitudes towards flex culture and awareness of the risks of consumer debt. Participants reported starting to implement family financial planning, reducing impulse purchases based on social media trends, increasing deliberation with partners regarding consumption decisions, and instilling the value of simple living in their children. Daily diary data reflect a decrease in the frequency of purchasing non-primary goods and an increase in the practice of periodically evaluating consumption at the family level. This program produces a model of mentoring Muslim women based on tarbiyah values ​​and family ecology which is oriented towards strengthening the economic, social and spiritual resilience of families, as well as providing practical contributions to the development of community-based Islamic education management in response to consumer culture and flex culture.